Climate Change Effect on Irrigation Water Requirement of Wheat and Maize in Northern Part of Bangladesh - Haque, Md Panjarul; Hossain, Md Zakir; Ali, Muhammad Ahsan (International Journal of Climate Research, 2021)
Bangladesh is one of the most vulnerable countries for climate change in agricultural water management. A research had been done to assess climate change effects on irrigation water use of wheat and maize in the northern part of Bangladesh. The twenty nine years of data (1990-2018) were analyzed with Mann-Kendall test as well as Sen’s slope for climate change impact and the responsible weather parameters due to climate change were identified with correlation coefficients. The crop water requirement of wheat in Bogura and Rangpur was declining at the rate of 3.3mm and 2.3mm per decade respectively. Net irrigation water requirement of wheat at both Bogura and Rangpur was inclining at the rate of 1mm and 10mm per decade respectively because the effective rainfall of these regions was decreasing at 5mm and 11mm per decade respectively. The crop water requirement of maize for similar districts was increasing at the rate of 3.2mm and 2.5mm per decade respectively although net irrigation water requirement had statistically non-significance for climate change effect. The weather parameter, which was mainly responsible for climatic change in irrigation water requirement, was increasing temperature. Therefore, wheat cultivation might be coped with climate change in the northern part of Bangladesh rather than maize on the basis of irrigation and water management.